Lactic Acid-Producing Probiotic Saccharomyces cerevisiae Attenuates Ulcerative Colitis via Suppressing Macrophage Pyroptosis and Modulating Gut Microbiota - Sun, Siyuan; Xu, Xiuxiu; Liang, Ling; Wang, Xiaoli; Bai, Xue; Zhu, Lanping; He, Qijin; Liang, Huixi; Xin, Xin; Wang, Li; Lou, Chenxi; Cao, Xiaocang; et al. (Frontiers in Immunology, 2021)
Lactic acid, a metabolic by-product of host and intestinal microbiota, has been recovered as an active signal molecule in immune system. In this study, a novel lactic acid biosynthesis pathway that directly produced lactic acid from glucose rather than ethanol was reconstructed in Saccharomyces Cerevisiae (S. cerevisiae) with high production. The engineered S. cerevisiae showed anti-inflammatory activity in dextran sulphate sodium (DSS)-induced mice with improved histological damage, increased mucosal barrier and decreased intestinal immune response. Lactic acid regulated macrophage polarization state and promoted the expression of anti-inflammatory cytokines in vivo and in vitro. Increasing the macrophage monocarboxylic acid transporter mediated active lactate uptake suppressed the excessive activation of NLRP3 inflammasome and the downstream caspase-1 pathway in macrophage. Moreover, lactic acid promoted histone H3K9 acetylation and histone H3K18 lactylation. Meanwhile, the engineered S. cerevisiae altered the diversity and composition of intestinal microbiota and changed the abundance of metabolic products in mice with colitis. In conclusion, this study shows that application of engineered S. cerevisiae attenuates DSS-induced mice colitis via suppressing macrophage pyroptosis and modulating intestinal microbiota, which is an effective and safe treatment strategy for ulcerative colitis.